2022
DOI: 10.3390/ijms24010162
|View full text |Cite
|
Sign up to set email alerts
|

Scion-to-Rootstock Mobile Transcription Factor CmHY5 Positively Modulates the Nitrate Uptake Capacity of Melon Scion Grafted on Squash Rootstock

Abstract: It is generally recognized that the root uptake capacity of grafted plants strongly depends on the rootstocks’ well-developed root system. However, we found that grafted plants showed different nitrate uptake capacities when different varieties of oriental melon scion were grafted onto the same squash rootstock, suggesting that the scion regulated the nitrate uptake capacity of the rootstock root. In this study, we estimated the nitrate uptake capacity of grafted plants with the different oriental melon variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…In the other hand, the shoot-derived auxin and ELONGATED HYPOCOTYL5 (HY5) might also function as the shoot-root mobile signal to balance the shoot-root growth by coupling shoot growth and carbon assimilation with root growth and nutrient uptake (Ljung et al, 2015;Chen et al, 2016). In the melon-pumpkin grafts, the scion-to-rootstock mobile HY5 signal positively modulated the nitrate uptake capacity of rootstock roots (Hou et al, 2022). Also, and for obtaining the energy necessary for meristem proliferation (Xiong et al, 2013;Li et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…In the other hand, the shoot-derived auxin and ELONGATED HYPOCOTYL5 (HY5) might also function as the shoot-root mobile signal to balance the shoot-root growth by coupling shoot growth and carbon assimilation with root growth and nutrient uptake (Ljung et al, 2015;Chen et al, 2016). In the melon-pumpkin grafts, the scion-to-rootstock mobile HY5 signal positively modulated the nitrate uptake capacity of rootstock roots (Hou et al, 2022). Also, and for obtaining the energy necessary for meristem proliferation (Xiong et al, 2013;Li et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, along with the cultivation, participate soil organic-matter changes accordingly [23]. Scion and rootstock transportation modulates nitrate uptake capacity [24]. Biomass partitioning of Macadamia with high manganese and low phosphorus concentrations showed that dry weight of roots, stems, branches and leaves accounted for 14-20%, 19-30%, 36-52%, and 12-18% of total plant weight, respectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is known that the scion can also affect the rootstock [ 78 , 79 ], we analyzed the possible movement in both directions. β-glucuronidase activity was stable in the transgenic parts of the grafted plants for 10 years in the greenhouse and in the field, but no transfer through grafting in any direction was detected.…”
Section: Discussionmentioning
confidence: 99%